Solitary and multiple simultaneous malignant epithelial mammary tumours in dogs: An explorative retrospective study. (March 2021) - Pecile, A.; Groppetti, D.; Ferrari, R.; Grieco, V.; Giudice, C.; Spediacci, C.; Stefanello, D.; Boracchi, P.
Abstract: Canine mammary tumours represent a hard-prognostic task for veterinary clinicians. TNM staging and grading systems refer to a single tumour. Significant limits come to light when these systems are applied to multiple mammary tumours due to the arbitrary criterion in determining which single tumour is representative of the patient's prognosis. This study explored some clinical features of 50 dogs affected by at least one malignant mammary tumour. Clinical features and staging, together with histological classification and grading, have been related to disease-free survival (DFS) with the purpose to evaluate their impact on prognosis. The prognosis was worse in 10-11-year-old dogs (P < 0.05), in dogs affected by complex carcinoma (P < 0.05), and in patients assigned to Peña grade I (P < 0.05). The bodyweight was not linearly related to DFS (P < 0.01), and patients with a low number of neoformations (n ≤ 2) showed a better prognosis than dogs with 3–5 tumours (P < 0.05). Both the average and the total size of malignant tumours were related to DFS (P < 0.05). Dogs assigned with stage I had the best DFS (P < 0.05). In conclusion, the Peña grade I alone would not seem to guarantee a favourable prognosis when applied to mammary tumours in dogs affected by multiple simultaneous presentations. Different characteristics, besides tumour grading, such as tumour immunophenotype and expression of hormonal receptors, could in the future, contribute to elucidate the clinical behaviour of multiple canine mammary tumours. Highlights: Grading alone seems not reliable to predict prognosis of multiple mammary tumours. The size of multiple tumour require further in-depth speculative models. Necrosis and infiltrative tumour growth could influence prognosis.